Analysis of Nodal Diameter Zero Blade Vibrations of a Radial Turbine - Markus Wunderlich; Alexander Esper; Manfred Wirsum; Klaus Buchmann (International Journal of Turbomachinery, Propulsion and Power, 2020)
This paper presents results of strain gauge measurements, which have been carried out on a full-scale turbocharger test rig. Rotational speed of the turbocharger was ramped up and down through four preliminary anticipated rotor-blade resonances, with a known combination of main order of excitation and corresponding nodal diameter. An analysis of the transient data is presented. An investigation of spectra with high frequency resolutions, centered on individual blade resonance points in time, is presented. In contrast to former research, all blades resonate at the same point in time and thus at the same resonance frequency, if the excitation corresponds to a nodal diameter of zero. Strain data from the shaft is used to support findings, which, in other publications, often solely rely on strain data from individual blades.